The influence of managers’ communication styles on employees’ job satisfaction among local and expatriate managers / Abdul Kadir Othman … [et al.] - Othman, Abdul Kadir; Hamzah, Muhammad Iskandar; Abdullah, Zaini; Abdul Rahim, Nooraini (Universiti Teknologi MARA Cawangan Selangor, 2015)
In today’s borderless business environment, companies are operating in different locations across the globe to ensure that they can gain competitive advantage over their competitors at different countries. To ensure common strategic mission, vision and objectives of the company across the globe, managers from different countries of origin are sent to different countries to equip them with a global mindset in managing the company. The problem is that they have different ways of communication as compared to local managers. These might affect the level of job satisfaction of employees. This study was intended to investigate the influence of different communication styles of expatriate and local managers on employees’ job satisfaction in manufacturing companies in Malaysia. From the analysis of 170 data collected from the employees, the results indicate that telling, selling and joining communication styles of local managers are the significant predictors of employees’ job satisfaction. For expatriate managers, only selling communication style contributes significantly to the level of employees’ job satisfaction. The implications of the study are discussed in detail in the paper.